Observational and genetic associations between cardiorespiratory fitness and cancer: a UK Biobank and international consortia study - Watts, EL; Gonzales, TI; Strain, T; Smith-Byrne, K (Springer Nature, 2023)
Background The association of fitness with cancer risk is not clear.